2015
DOI: 10.1111/1911-3846.12151
|View full text |Cite
|
Sign up to set email alerts
|

Tax Avoidance and the Implications of Weak Internal Controls

Abstract: I examine whether corporate tax avoidance is associated with internal control weaknesses (ICWs) disclosed under the Sarbanes-Oxley Act (SOX). ICWs disclosed under SOX are frequently related to a firm's tax function. When pervasive ICWs exist, the likelihood increases that these frequent tax-related ICWs spill over from financial reporting issues to tax avoidance objectives. Thus, my research helps corporate stakeholders understand the implications of internal controls beyond simply financial reporting objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(72 citation statements)
references
References 50 publications
(93 reference statements)
4
64
0
4
Order By: Relevance
“…While prior studies have shown that effective internal control mitigates information risk, our study extends this line of research by documenting that effective internal control can further improve firm operational efficiency. Our study hence adds to the emerging literature that examines the implications of internal control beyond financial reporting quality (e.g., Cheng et al ; Feng et al ; Bauer ). The evidence in this article contributes to the ongoing debate on the costs and benefits of SOX 404 reporting.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…While prior studies have shown that effective internal control mitigates information risk, our study extends this line of research by documenting that effective internal control can further improve firm operational efficiency. Our study hence adds to the emerging literature that examines the implications of internal control beyond financial reporting quality (e.g., Cheng et al ; Feng et al ; Bauer ). The evidence in this article contributes to the ongoing debate on the costs and benefits of SOX 404 reporting.…”
Section: Introductionmentioning
confidence: 73%
“…Cheng et al () find that material weaknesses lead to lower investment efficiency. Bauer () finds that tax‐related material weaknesses are associated with higher effective tax rates, suggesting that these material weaknesses reduce the effectiveness of firms' tax planning. Feng et al () investigate whether ineffective internal control over inventory affects inventory management.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, firms with tax-related ICMWs may lack sufficient understanding and/or control over the tax function to manage earnings. Consistent with this alternative, Bauer (2016) finds that firms with tax-related ICMWs are not effective tax planners because ineffective internal controls over the tax function inhibit management's understanding of tax positions and tax planning opportunities. These firms improve their tax planning effectiveness once the tax-related ICMWs are remediated.…”
Section: Hypothesesmentioning
confidence: 95%
“…Trabalhos mais recentes têm destacado a influência de algumas características da empresa no seu perfil agressividade fiscal, são elas: a qualidade do ambiente informacional da empresa (Gallemore & Labro, 2015); a demora na publicação das demonstrações (Rodrigues, 2017); a predisposição para refazimento de demonstrações financeiras (Ramos, 2017); a eficiência dos mecanismos de controle interno (Martinez, Ribeiro & Funchal, 2015;De Simone, Ege & Stomberg, 2015;Bauer, 2016), a eficiência empresarial na utilização dos recursos (Paste Junior, 2017); as estratégias de negócios e os ciclos de vida das empresas (Higgins, Omer & Phillips, 2015;Silva & Rezende, 2017); as restrições financeiras as quais as empresas estão submetidas (Law & Mills, 2015;Edwards, Schwab & Shevlin, 2016;Da Silva & Martinez, 2017;Richardson, Taylor & Lanis, 2015); as transações com partes relacionas no exterior ; e a utilização dos paraísos fiscais como mecanismo para redução da tributação explícita (Lee, 2017;Dyreng & Lindsey, 2009;Dyreng, Lindsey, Markle & Shackelford, 2015;Taylor & Richardson, 2012). Esses estudos buscam identificar características das firmas que conduzem uma maior ou menor agressividade tributária.…”
Section: Características Das Firmasunclassified